Obstinate rigour: Populism without apologies authors’ reply to critics - Cadahia, Luciana (2023)
In this article we offer a response to each of the authors who participated in the exchange. But instead of responding to each one separately, we decided to organise our writing around three themes. In the first place, we propose an intellectual, militant and biographical description that helps to put the original motivations of our book Seven Essays on Populism into context. Secondly, we offer a reflection on the role of ontology in our text, paying special attention to the critiques made by Barros & Martínez Prado, Bosteels and Marchart. Thirdly, we conclude with a deepening of the link between populism and feminism, paying special attention to the lucid observations of Barros & Martínez Prado and Gunnarsson-Payne.